The effects of free-fare public transportation on the total active travel in children: A cross-sectional comparison between two Finnish towns. (December 2022) - Pesola, A.J.; Hakala, P.; Berg, P.; Ramezani, S.; Villanueva, K.; Rinne, T.
Abstract: Background: Free-fare public transport policies potentially increase walking to transport stops, but may replace other active travel modes with unknown effects on total active travel. We compared active travel behaviour of children living in a Finnish city with a free-fare public transport to a reference city. Methods: Children were recruited from primary school grades 4–6 in 21 participating schools, located in 11 neighborhood pairs from Mikkeli (free-fare bus) and Kouvola (no free-fare bus). Children marked all places they visited the previous week, visit frequency, and travel modes into a participatory mapping survey during a lesson. Active travel was assessed as a sum of all round-trips from home to destination by walking (4 km/h), walking-to-bus-stop, skating/scooting (7 km/h) and cycling (10 km/h). Active travel was compared between cities with linear mixed effects models. Results: A total of 427 children respondents (age mean and SD 11.0 ± 0.8 years) marked altogether 2445 places. On average they visited 5.7 ± 2.2 places 13.8 ± 7.2 times during the week. Median trip distance was 521 m by walking, 1794 m by bike, and 730 m by walking to bus stop. A total of 23.3% and 43.5% of children in Mikkeli (bus 6.4%; bike 30.0% of all trips) and 12.9% and 59.2% in Kouvola (bus 2.1%; bike 44.5% of all trips) marked ≥5 bus and cycling trips per week, respectively (city p ≤ 0.006). Children in Mikkeli gained more active travel from walking to bus stops, and children in Kouvola from cycling (P < 0.001). Estimated total active travel was 3.19 h/week (95% CI 2.62–3.83) in Mikkeli and 3.33 h/week (2.74–3.97) in Kouvola (P = 0.749). Conclusions: Children living in a Finnish city with free-fare bus cycle less, but walk more to bus stops, and have a similar total active travel duration as compared to children who do not have a free-fare bus option for all their everyday trips. Walking to public transport is a significant source of active travel and free-fare policy can facilitate this behaviour. Graphical abstract: Image 1 Highlights: Free-fare transport was not associated with changes in total active travel. Children eligible for free-fare transport were cycling less, but walking more to bus stop. Walking to bus stop was a significant source of active travel. Total public transport use share was small (6%).